(NlOG)QÆKA WIW^ENNQ TEMI (B"æ(NNFORMACÆQ(B" /s)E - (NsAGAN(B, (No(B.,s; (NmIKIT@K(B, (Ns(B.s (2017)
(NzA NOWO@ PROGRAMO@ PER[)QÆ UROKI ÆNFORMATIKI PRISWQ^ENÆ OZNAJOMLENN@ DÆTEJ Z PONQTTQM (B"Æ(NNFORMACÆQ(B", (NQKU TRAKTU@TX QK DEQKÆ WÆDOMOSTÆ(B, (NZNANNQ(B, (NWÆDOBRAVENNQ L@DINO@ OTO^U@^OGO SWÆTU(B.s)E
(Nb)QÆBLÆOGR(B.: 8 (NNAZW(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: )Qæ(NNFORMATIKAs)E -- (NMETODIKA WIKLADANNQs -- (NDIDAKTI^N)QÆ MATERÆALIs)E -- (NPO^ATKOWA [KOLAs; )QÆ(NNFORMATIKAs)E; (NMETODIKA WIKLADANNQs; (NDIDAKTI^N)QÆ MATERÆALIs)E; )QÆ(NNTERAKTIWNA GRAs)E; (NWPRAWIs; (NREBUSIs; (NPO^ATKOWA [KOLAs